Queer Position: A Study on the Psychosocial Acceptance of Queer People and Their Issues in India with Reference to Hansal Mehta’s Aligarh - M. PRIYAKUMARAN; S. MEENAKSHI (International Journal of Psychosocial Rehabilitation, 2020)
This paper tends to analyse the psychosocial imbalance between a homosexual character and his inner conflict, which ends with uncertain death. It has tried to bring back the communal distance of a homosexual character in India. Prof. Siras is identified as a queer character eventually faces enormous unsolved problem due to his indifferent identity. Besides the investigation on homosexual character’s inner conflict with the reference to the historical background and scientific suggestion, the reception of social perspective also examined. Depth picture of Siras’ conflict between life and death has been identified through continues reading which has proved the forces by the society which leads to death. So the paper has proven the prolong disturbance of psyche may cause to ending life.